Gender-based difference in early mortality among patients with ST-segment elevation myocardial infarction: insights from Kermanshah STEMI Registry - Siabani, Soraya (J Cardiovasc Thorac Res, 2020)
Introduction: This study aimed to evaluate the in-hospital mortality of patients with ST-segment elevation myocardial infarction (STEMI), according to gender and other likely risk factors. Methods: This study reports on data relating to 1,484 consecutive patients with STEMI registered from June 2016 to May 2018 in the Western Iran STEMI Registry. Data were collected using a standardized case report developed by the European Observational Registry Program (EORP). The relationship between in-hospital mortality and potential predicting variables was assessed multivariable logistic regression. Differences between groups in mortality rates were compared using chi-square tests and independent t-tests. Results: Out of the 1484 patients, 311(21%) were female. Women were different from men in terms of age (65.8 vs. 59), prevalence of hypertension (HTN) (63.7% vs. 35.4%), diabetes mellitus (DM) (37.7% vs. 16.2%), hypercholesterolemia (36.7% vs. 18.5%) and the history of previous congestive heart failure (CHF) (6.6% vs. 3.0%). Smoking was more prevalent among men (55.9% vs. 13.2%). Although the in-hospital mortality rate was higher in women (11.6% vs. 5.5%), after adjusting for other risk factors, female sex was not an independent predictor for in-hospital mortality. Multivariable analysis identified that age and higher Killip class (≥II) were significantly associated with in-hospital mortality rate. Conclusion: In-hospital mortality after STEMI in women was higher than men. However, the role of sex as an independent predictor of mortality disappeared in regression analysis. The gender based difference in in-hospital mortality after STEMI may be related to the poorer cardiovascular disease (CVD) risk factor profile of the women.